Can We Distinguish Triphasic Waves From Other Generalized Periodic Discharges? Do We Need to?. Issue 5 (September 2021) - Foreman, Brandon
Abstract : Summary: Triphasic waves are intuitively distinctive waveforms that fall under the umbrella of generalized periodic discharges. The ability to distinguish these waveforms consistently could be helpful if a specific underlying pathophysiology could be identified. However, scalp EEG and clinical observation have been limited in their ability to elucidate the underlying cortical physiology that leads to triphasic waves. Evidence from intracranial physiologic data and computational modeling suggest that these and other periodic discharges should be viewed not as strictly ictal nor non-ictal but rather on the spectrum between these two. Triphasic waves in particular appear to result from an abnormal balance between cortical excitation and synaptic transmission with input from functionally connected brain networks, such as the thalamocortical pathways involved in arousal. The practical implication of triphasic waves begins with acknowledgement of uncertainty and a rational approach should ask whether the pattern—or its treatment–might be creating harm.